Want to see my report, coach? Sport science reporting in the real world - Buchheit, M. (ASPETAR Sports Medicine Journal, 2017)
On the 9 March 2013, Sir Alex Ferguson delivered in the Irish Times probably one of the most encouraging ever message for sport scientists in football: "Sports science, without question, is the biggest and most important change in my lifetime. It has moved the game onto another level that maybe we never dreamt of all those years ago. Sports Science has brought a whole new dimension to the game". While such statements are gold for universities advertising sport sciences courses all over the world and for young students willing to embrace their carrier in elite clubs, the actual value of sport science may not always be rated as high in some elite clubs or federations. Having an impact on the training programme, as a sport scientist, is anything but easy. The way coaches and athletes understand, accept and use sport science is highly variable and unpredictable. The path leading to effective sport science support is a long and winding road, with frequent stops and constant redirections required. Historically, many mistakes have been made while we learned about the veracity and usefulness of our data and the best ways to report and implement sports science in the elite sports setting.